New insights into trypanosomatid U5 small nuclear ribonucleoproteins - da Silva, Marco Tulio A. [UNESP]; Ambrosio, Daniela L. [UNESP]; Trevelin, Caroline C. [UNESP]; Watanabe, Tatiana F. [UNESP]; Laure, Helen J.; Greene, Lewis J.; Rosa, Jose C.; Valentini, Sandro Roberto [UNESP]; Cicarelli, Regina Maria Barretto [UNESP] (Fundacão Oswaldo Cruz, 2011)
Several protozoan parasites exist in the Trypanosomatidae family, including various agents of human diseases. Multiple lines of evidence suggest that important differences are present between the translational and mRNA processing (trans splicing) systems of trypanosomatids and other eukaryotes. In this context, certain small complexes of RNA and protein, which are named small nuclear ribonucleoproteins (U snRNPs), have an essential role in pre-mRNA processing, mainly during splicing. Even though they are well defined in mammals, snRNPs are still not well characterized in trypanosomatids. This study shows that a U5-15K protein is highly conserved among various trypanosomatid species. Tandem affinity pull-down assays revealed that this protein interacts with a novel U5-102K protein, which suggests the presence of a sub-complex that is potentially involved in the assembly of U4/U6-U5 tri-snRNPs. Functional analyses showed that U5-15K is essential for cell viability and is somehow involved with the trans and cis splicing machinery. Similar tandem affinity experiments with a trypanonosomatid U5-Cwc21 protein led to the purification of four U5 snRNP specific proteins and a Sm core, suggesting U5-Cwc-21 participation in the 35S U5 snRNP particle. of these proteins, U5-200K was molecularly characterized. U5-200K has conserved domains, such as the DEAD/DEAH box helicase and Sec63 domains and displays a strong interaction with U5 snRNA.
Keywords: trans splicing; cis splicing; U5 snRNP; U5-Cwc-21; PTP-Tag; Trypanosoma cruzi; Trypanosoma brucei